Root respiration, growth and nitrogen uptake of Quercus suber seedlings - Mata, C; Scheurwater, I; MartinsLoucao, M A; Lambers, H (PLANT PHYSIOLOGY AND BIOCHEMISTRY, 1996)
We tested the influence of two N-sources, NO3- and NH4+, on root growth and respiration of Quercus suber L. Seedlings were grown on hydroponics with 0.5 mM N as NO3- or NH4+ in a growth chamber. Root relative growth rate (RGR) of NO3--fed seedlings ranged from 9 to 34 mg g(-1) day(-1). These values are lower than those described for slow-growing herbaceous and for most woody species. Root respiration and the activity and capacity of the alternative pathway (AP) showed no differences between the two N-sources. Both activity and capacity of the AP were very low and the cytochrome pathway was fully engaged. Specific respiratory costs were calculated for maintenance, 6.3 nmol O-2 g(-1) s(-1), for nitrate uptake, 0.99 mol O-2 mol N-1, and for growth 5.4 mmol O-2 g(-1). These values are similar to those found for slow-growing herbaceous species. The major part of total root respiration, over 64%, was used for maintenance processes, and a much smaller fraction for growth and nitrate uptake.
Keywords: NH4+; NO3-; Relative growth rate; root respiration